Study on herd life traits of culled and disposed Kankrej cattle at organized farms - KJ Ankuya; KB Prajapati; BK Ashwar; Tyagi; NK Pareek (Journal of Livestock Biodiversity, 2025)
An analysis was performed to study the herd life traits of culled and disposed Kankrej cattle at organized farms of Gujarat State. Data were collected from different disposal and production registers for the period from January 2003 to December 2013 and these were analyzed by using General Linear Model (GLM) procedure in the SPSS statistical software (version 20.0). The least squares analysis of disposed Kankrej cows at organized farms was performed to study on various life time traits like Age at First Calving, Number of Lactations Completed, Total Lactation Days, Life time Milk Yield, Herd Life, Herd Productive Life, Herd Unproductive Life, Milk Yield Per Day of Productive Life and Milk Yield Per Day of Herd life. The overall least squares means for above mentioned life time traits in Kankrej cows were 1548.12 ± 11.26 days, 3.29 ± 0.10 number, 1012.58 ± 30.66 days, 6427.01 ± 229.67 kg, 3225.91 ± 49.70 days, 1745.20 ± 86.62 days, 1174.63 ± 23.56 days, 3.73 ± 0.06 kg and 1.74 ± 0.04 kg, respectively for Kankrej herd of organized farm.